Speed Control of Direct Torque Controlled Induction Motor By using PI, Anti-Windup PI And Fuzzy Logic Controller - AÇIKGÖZ, Hakan; KECECIOGLU, O. Fatih; GANI, Ahmet; SEKKELI, Mustafa (International Journal of Intelligent Systems and Applications in Engineering, 2014)
In this study, comparison between PI controller, fuzzy logic controller (FLC) and an anti-windup PI (PI+AW) controller used for speed control with direct torque controlled induction motor is presented. Direct torque controlled induction motor drive system is implemented in MATLAB/Simulink environment and the FLC is developed using MATLAB/Fuzzy-Logic toolbox. The proposed control strategy is performed different operating conditions. Simulation results, obtained from PI controller, FLC and PI+AW controller showing the performance of the closed loop control systems, are illustrated in the paper. Simulation results show that FLC is more robust than PI and PI+AW controller against parameter variations and FLC gives better performance in terms of rise time, maximum peak overshoot and settling time.